Study of tribological properties of lubricating oil blend added with graphene nanoplatelets - Azman, S.S.N.; Zulkifli, Nurin Wahidah Mohd; Masjuki, Haji Hassan; Gulzar, M.; Zahid, R. (Materials Research Society, 2016)
This paper investigates the effects of graphene nanoplatelets (GNPs) as additives in palm-oil trimethylolpropane (TMP) ester blended in polyalphaolefin. Different concentrations of GNPs that were ultrasonically homogenized in blended lubricants consist of 95 vol% polyalphaolefin and 5 vol% TMP ester. Physical properties of the nanolubricants were identified and tribological behaviors of GNP in blended lubricants were studied using standard fourball testing and surface analysis was done on the wear surfaces using scanning electron microscopy and energy-dispersive X-ray techniques. Addition of 0.05 wt% GNP in blended lubricant resulted in the lowest coefficient of friction and wear scar diameter, thus selected as the most suitable concentration of GNP in the blended lubricant. Friction and wear were reduced by 5 and 15% respectively, with the presence of 0.05 wt% GNP in the blended lubricant.